PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI BANGUN RUANG KUBUS DAN BALOK DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS 5 SD - Herdian Dwi Rusdianto; Meirza Nanda Faradita; Iswahyuni (Universitas Muhammadiyah Surabaya, 2024)
The aim of this research is to improve mathematics learning outcomes in Building Space material through the Problem Based Learning model for fifth grade students at Khadijah Elementary School for the 2023/2024 academic year. The form of this research is classroom action research, using a cycle model. Each cycle consists of four stages, namely planning, implementation, observation and reflection. Data collection techniques use observation, tests, documentation and interviews. Data validity uses triangulation techniques of sources, methods, investigators and theories as well as content validity. The performance indicator determined is that at the end of the cycle students who reach the KKTP (score 70) are 80% of the number of class V students. The data analysis technique uses comparative and critical descriptive analysis. The research procedure consists of two cycles, and each cycle consists of planning, action, observation or observation and reflection. The research results concluded that the Problem Based Learning (PBL) model could improve mathematics learning outcomes for fifth grade students at Khadijah Elementary School, Surabaya in 2023/2024. This is shown by the student learning results in cycle I, the highest score was 78 and the lowest score was 55, 6 students (31. 58%) achieved the KKTP with an average of 63. 11. In cycle II the student learning outcomes were the highest score of 85 and the lowest score of 70, 19 students (100%) achieved the KKTP with an average of 76. 32